2016
DOI: 10.1038/ncomms10346
|View full text |Cite
|
Sign up to set email alerts
|

C1q acts in the tumour microenvironment as a cancer-promoting factor independently of complement activation

Abstract: Complement C1q is the activator of the classical pathway. However, it is now recognized that C1q can exert functions unrelated to complement activation. Here we show that C1q, but not C4, is expressed in the stroma and vascular endothelium of several human malignant tumours. Compared with wild-type (WT) or C3- or C5-deficient mice, C1q-deficient (C1qa−/−) mice bearing a syngeneic B16 melanoma exhibit a slower tumour growth and prolonged survival. This effect is not attributable to differences in the tumour-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
223
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(253 citation statements)
references
References 66 publications
10
223
2
2
Order By: Relevance
“…Irrespectively of the beneficial or harmful impact that the complement system has on tumor growth, the C1q molecule's contribution to tumor progression and metastasization has been demonstrated regardless of complement activation, both in prostatic cancer cells 15,35 and very recently in melanoma. 31 These results provide a new perspective on our previously published data which demonstrated that the neuT upregulation on tumor cells observed in neuT-C3KO tumors was not only directly dependent on lack of C3 activation. In particular, the extremely aggressive phenotype displayed by neuT-C3KO tumors can also be caused by the impaired activation of WWOX, which is a result of the unexpected lack of C1q deposition on the tumor site of neuT-C3KO mice.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Irrespectively of the beneficial or harmful impact that the complement system has on tumor growth, the C1q molecule's contribution to tumor progression and metastasization has been demonstrated regardless of complement activation, both in prostatic cancer cells 15,35 and very recently in melanoma. 31 These results provide a new perspective on our previously published data which demonstrated that the neuT upregulation on tumor cells observed in neuT-C3KO tumors was not only directly dependent on lack of C3 activation. In particular, the extremely aggressive phenotype displayed by neuT-C3KO tumors can also be caused by the impaired activation of WWOX, which is a result of the unexpected lack of C1q deposition on the tumor site of neuT-C3KO mice.…”
Section: Discussionsupporting
confidence: 69%
“…It has been demonstrated that cancer cells establish a balance between complement activation and inhibition. 29 However, controversial and conflicting data on the complement system's tumor-promoting, 30,31 and inhibiting activities, 24 have been published, 2 and the mechanisms of complement-specific activities in the tumor microenvironment are still unclear and demands further study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a wide range of immunomodulatory functions of C1q have become evident that are independent of its involvement in the complement activation (3,4); these include modulation of dendritic cell functions (5), cancer progression (6), and neuronal synapse pruning (7).…”
mentioning
confidence: 99%
“…Certaines protéines du complément comme le C1q et les anaphylatoxines C3a et C5a, peuvent participer à ce processus. Ainsi, dans le modèle de mélanome B16/F10 [26], les souris déficientes pour le gène codant le C1q présentent une croissance tumorale ralentie qui peut être reliée, notamment, à une densité du réseau vasculaire des tumeurs diminuée. Cet effet du C1q sur la vascularisation a également été rapporté dans des modèles in vitro utilisant des cellules endothéliales, mais également in vivo, dans le cadre de la pré-éclampsie [36] ou de la cicatrisation des plaies [37].…”
Section: Resultsunclassified
“…De récentes études ont en effet montré que le C1q et le CAM possédaient également des propriétés pro-mitogéniques et prométastatiques. Ainsi, dans le modèle murin syngénique de mélanome B16/F10 2 , la croissance tumorale observée chez des souris déficientes pour le gène codant C1q est ralentie et la survie des animaux est prolongée [26]. Le C1q agit directement sur les cellules tumorales dont il augmente l'adhérence, la migration et la prolifération.…”
Section: Protéines Du Complément Et Contexte Tumoralunclassified